2019
DOI: 10.1111/1751-7915.13512
|View full text |Cite
|
Sign up to set email alerts
|

Calcium transcriptionally regulates movement, recombination and other functions of Xylella fastidiosa under constant flow inside microfluidic chambers

Abstract: Summary Xylella fastidiosa is a xylem‐limited bacterial pathogen causing devastating diseases in many economically important crops. Calcium (Ca) is a major inorganic nutrient in xylem sap that influences virulence‐related traits of this pathogen, including biofilm formation and twitching motility. This study aimed to adapt a microfluidic system, which mimics the natural habitat of X. fastidiosa, for whole transcriptome analysis under flow conditions. A microfluidic chamber with two parallel channels was used, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 86 publications
(129 reference statements)
0
11
0
Order By: Relevance
“…Host adaptation in this pathogen is mainly facilitated by multiple inter-and intra-subspecific homologous recombination events that created new genotypes able to invade new ecological niches [58,59]. Wild-type and experimentally generated hybrids show that transformation frequency is variable among strains/subspecies and increases with the concentration of environmental calcium, the number of sympatric strains and the lineage age [21,58,59,108,110]. Horizontal gene transfer is well described in the American strains.…”
Section: Genetic Diversitymentioning
confidence: 99%
See 2 more Smart Citations
“…Host adaptation in this pathogen is mainly facilitated by multiple inter-and intra-subspecific homologous recombination events that created new genotypes able to invade new ecological niches [58,59]. Wild-type and experimentally generated hybrids show that transformation frequency is variable among strains/subspecies and increases with the concentration of environmental calcium, the number of sympatric strains and the lineage age [21,58,59,108,110]. Horizontal gene transfer is well described in the American strains.…”
Section: Genetic Diversitymentioning
confidence: 99%
“…Transcription control is environment-dependent and it should therefore be analyzed in vivo or in conditions that closely resemble natural settings to meaningfully represent the trait under analysis. As in planta studies are technically challenging in Xf, most analyses of gene expression in this bacterium have been performed in vitro in batch cultures, but this pathogen survives only in environments under continuous flow (xylem vessels and insects' feeding canal [17,110]). Whole transcriptome sequencing and qPCR in microfluidic chambers, which mimics the natural habitats of this bacterium, showed that gene expression and the regulatory role of environmental elements such as calcium are different between batch and flow settings [110].…”
Section: Gene Expression Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a general agreement that insect vectors hosting cells of X. fastidiosa in their foregut inoculate these bacterial cells into the xylem vasculature while feeding on the leaf petioles of the host plant, from where it spreads into the xylem of branches and stem ( Almeida 2016 ). Since xylem vessels conduct water from roots to leaves, X. fastidiosa is supposedly able to spread along the xylem vasculature by efficiently moving against sap flow ( Meng et al 2005 ; Chen and De La Fuente 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…By increasing the calcium concentration to 2 mM, they confirmed that the twitching speed was significantly increased. In addition, RNA‐seq determined that calcium regulated the transcription of genes related to the type IV pili mechanism, pathogenicity and host adaptation (Chen and De La Fuente, 2020 ).…”
Section: Microfluidic Devices With Linear Channelsmentioning
confidence: 99%